Optical quality of Fresnel-structured hyperopic implantable collamer lenses: A ray-tracing analysis - Kimiya Shimizu; Takushi Kawamorita (PLoS ONE, 2026)
To achieve positive refractive power, implantable collamer lenses (ICLs) for hyperopia increase central thickness, which in turn raises the risk of pupil blockage and lens contact in eyes with shallow anterior chambers. Additionally, incorporating a central hole raises concerns about stray light and halo formation due to increased thickness. This study used optical simulation to evaluate the imaging performance of hyperopic ICLs, highlighting the Fresnel structure’s potential to reduce thickness while maintaining imaging performance. Optical simulations were performed using Ansys Zemax OpticStudio 2024 R2 (Ansys, Inc.). An ICL with +10.00 D correction was designed for the Liou & Brennan model eye. The vault was set to 0.50 mm, and the central hole diameter was set to 0.36 mm. Fresnel ICLs (Fr. ICLs) with step heights ranging from 25 to 100 µm were compared with the reference ICL (Ref. ICL). Modulation transfer function (MTF) analyses were performed at internal artificial pupil diameters of 3.00 mm and 4.50 mm, both with and without holes. By reducing the central thickness from 0.80 mm to 0.40 mm, the Fr. ICL for hyperopia showed higher MTF values than the Ref. ICL at both pupil diameters. The difference was particularly significant at 4.50 mm. A slight MTF decrease due to the central hole was observed at 3.00 mm internal artificial pupil diameter. A step height of 50 µm or more suppressed contrast reduction at high spatial frequencies. Although further research is needed in illumination optics and clinical studies, ray-tracing simulations have demonstrated that the designed hyperopia-correcting Fr. ICL can reduce central thickness while maintaining or improving optical performance, making it a promising candidate for clinical application.